Putting Legal Restrictions Theory to the Test: An Arkansan Experiment, 1861-1863 - Marc D. Weidenmier; Richard C. K. Burdekin (Claremont McKenna College, Department of Economics, 2003)
During the Civil War the Arkansas legislature funded their expenditures primarily through interest-bearing warrants and war bonds. After these issues were made legal tender in November 1861, the discount attributed to them disappeared immediately and they began to circulate widely. By mid- 1862 they appeared to be preferred to Confederate notes - which were also made legal tender in November 1861 but required military intervention to support their acceptance. The widespread circulation and potential dominance of legal tender interest-bearing currency is consistent with legal restrictions theory. Confederate notes supplanted the Arkansas issues only after the legislature suspended interest payments in November 1862.
Keywords: N21; E42; 330; Legal restrictions; interest-bearing currency; civil war; Geldgeschichte; Währung; Finanzgeschichte; Arkansas